Numerical Study of the Aerodynamic Effect of Ski Suit Surface Roughness on Ski Jumping Athletes During the Flight Phase - K. Liu; Z. Wang; Q. Liu (Journal of Applied Fluid Mechanics)
Surface roughness of ski suits can have a significant effect on the aerodynamic performance of ski jumping athletes. Herein, several typical surface roughness configurations are examined through numerical simulations. Force parameters such as lift, drag and pitching moment are analyzed to evaluate the aerodynamic performance of varying surface roughness. Furthermore, the athlete model is segmented into distinct body parts to conduct a comprehensive analysis of the aerodynamic contributions from each individual segment. Generally, the surface roughness has a significant effect on the aerodynamic performance during the flight phase. Specifically, the lift-drag ratio of the entire multibody system shows a trend of increasing first and then decreasing. Moreover, the trunk of the athlete plays a predominant role in generating aerodynamic forces during the flight phase. Therefore, when designing high-performance ski jumping suits, prioritizing the surface roughness of this part can be considered first. Flow structures are also presented to analyze the impact of these various surface roughness conditions. Notably, flow suppression near the back region of the athlete body can significantly reduce the resistance force in the horizontal direction. Consequently, this revelation of the impact mechanism of ski suit surface roughness on the aerodynamic performance of the multibody system can guide the design of appropriate ski suits, and will also assist athletes in achieving superior aerodynamic performance during flight.